2022
DOI: 10.3390/jcm11092468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Xanthine Oxidase Inhibitors in Lowering Serum Uric Acid in Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: Objective: Current guidelines for gout recommend a treat-to-target approach with serum uric acid (SUA). However, there is little evidence for the dose-dependent effects of urate-lowering therapy (ULT). Herein, we analyzed the reported SUA-lowering effect and SUA target achievement differences for various doses of xanthine oxidase inhibitors. Methods: Approved ULT drugs were selected from the FDA Drug Database. We included prospective randomized controlled trials of ULT drugs from ClinicalTrials.gov, articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Lee yojin and etal evaluated that an equivalent outcome would be achieved by febuxostat 83.33 mg or topiroxostat 150 mg [3] . Kazuomi Kario in his study on Comparative effects of topiroxostat and febuxostat on arterial properties in hypertensive patients with hyperuricemia gave febuxostat and topiroxostat at dosages of 10-60mg/dl and 40-160mg/dl respectively [4] .…”
Section: Interventionsmentioning
confidence: 99%
“…Lee yojin and etal evaluated that an equivalent outcome would be achieved by febuxostat 83.33 mg or topiroxostat 150 mg [3] . Kazuomi Kario in his study on Comparative effects of topiroxostat and febuxostat on arterial properties in hypertensive patients with hyperuricemia gave febuxostat and topiroxostat at dosages of 10-60mg/dl and 40-160mg/dl respectively [4] .…”
Section: Interventionsmentioning
confidence: 99%
“…However, intracellular uric acid has been linked to elevated inflammation and heightened oxidative stress ( 4 ). Extensive research has identified high serum uric acid levels as an independent risk factor for various chronic kidney and joint disorders ( 5 ), including gout ( 6 ), chronic arthritis ( 7 ), joint deformity, and uric acid kidney stones ( 8 ), as well as chronic metabolic diseases such as hypertension ( 9 ), diabetes ( 10 ), and metabolic syndrome, along with cardiovascular disease ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In lieu of these drugs, xanthine oxidase inhibitors (XOIs) act by inhibiting the xanthine oxidase production which ultimately decreases the uric acid production. Uric acid-lowering drugs reduce oxidative stress and lower the inflammation caused by an accumulation of urate crystals [2]. Thus, curbing hyperuricemia with XOIs may assist in regression or even arrest the progression of CKD [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used XOI is allopurinol, which is an analog of hypoxanthine and xanthine; it competes with these molecules in binding xanthine oxidase and inhibits the formation of uric acid. Another is febuxostat, which non-selectively inhibits oxidized and reduced forms of xanthine oxidase [2]. Hence, we conducted this study to compare the renoprotective effects of febuxostat and allopurinol in CKD patients with hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%